If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -35 + 25 = -5x + 7x Combine like terms: -35 + 25 = -10 -10 = -5x + 7x Combine like terms: -5x + 7x = 2x -10 = 2x Solving -10 = 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + -2x = 2x + -2x Combine like terms: 2x + -2x = 0 -10 + -2x = 0 Add '10' to each side of the equation. -10 + 10 + -2x = 0 + 10 Combine like terms: -10 + 10 = 0 0 + -2x = 0 + 10 -2x = 0 + 10 Combine like terms: 0 + 10 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| -11t+-3=-14 | | 30x-33x=5-8 | | 30x^4-5x^3-10x^2=0 | | m-14=45 | | 7x+-5=11 | | t+25=32 | | (3x-9)(x+5)=x | | 8x+66=x | | 3x+2=15+3x | | 7[2-(3+4x)]*-2x=-9+2(1-15x) | | (5u+9)(1-u)=0 | | 5x=2y+8 | | 7[2(3+4x)]2x=9+2(115x) | | V=8212 | | y=4x^2+10x+5 | | 9x+10y=30 | | 1+2x/x=x-2/-3 | | (1/5)((5/2)x-10)=4(x+3) | | 4x^5-12x+9=0 | | 5x+-3y=12 | | 5x^2-100x+455=0 | | 7(x+5)-8=31-5x-4+12x | | 4x+2y+z=175 | | -3+8(x-3)=15x+2-7x | | 3-2x-(-7)=4x+10 | | -9-4=-7+x | | 6x^2+36x+18=0 | | 7(a-7)+18=5(a-5) | | 6(2x+-1)+3=x+7 | | 3(6n-4)+9n= | | 3x^2+72x+402=0 | | 5+3x+(-3)=x-(-4) |